Strategi Komposisi Paket Wisata dalam Rangka Mendukung Edukasi Pariwisata Berbasis Desa pada Gen Z Studi Kasus di Koperasi Desa Wisata Candirejo Kabupaten Magelang - Aulia Azzahra; Widhian Hardiyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The motivation behind this study is to examine the possible piece of visit bundles for age z in light of a legitimate concern for instructive the travel industry by considering the purposes behind picking vacationer locations. This study utilizes a quantitative methodology that gets information through the dispersion of online surveys including age z to decide the impact of every part. This shows that age z has an interest in chatting with visit bundles in towns that teach age z, so the Candirejo The travel industry village Agreeable should deal with the accessible visit bundles well in order to welcome youthful vacationers to visit and need to learn new societies in the town. Candirejo the travel industry town is a travel industry situated in Candirejo Village, Borobudur Locale, Magelang Rule, Focal Java Region. The consequences of this study got information, among others: 1) visit bundle factors influence the interest and choice to visit z-type travelers to foster information, 2) the travel industry interest factors and vacationer visits decidedly affect visit bundles, with additional interest and visiting choices of sightseers to visit Candirejo The travel industry village, and 3) together there is a positive and huge impact on every variable to impact choice to visit Candirejo The travel industry village.